Greek Folk Dance Systematic Participation Affects Quality of Life in Young and Middle Age Adults - Bougiesi, Μαρία; Zisi, Βασιλική; Gregoriou, Στεφανία; Pollatou, Ελιζάνα (Inquiries in Physical Education and Sport, 2011)
Dance and mainly Greek traditional dance comprise a significant form of physical activity for many Greeks of different ages. The purpose of the present study was to investigate the effects of adults’ systematic participation in traditional dance classes on factors of quality of life at different age level. The participants were 300 persons from two age groups (20-44, 45-65 years old). They were randomly selected an equal number of three subgroups traditional dancers, exercisers and non exercisers. The participants completed the Greek version of the SF-36 questionnaire for quality of life (Anagnostopoulos, Niakas, &Pappa, 2005). Multivariate analyses showed that ,there was a significant main effect of age in the factors of physical functioning (p<.001) and general health (p<.05). The younger scored better than the older and in the factors of social functioning (p<.001) and role emotional (p<.01) with the older scoring higher. There was also a significant main effect of the group with dancers scoring significantly higher from two other groups on the factors of body pain (p<.001), role emotional (p<.001) and mental health (p<.001) and significantly higher than the non exercisers on physical role (p<.05), general health (p<.01), vitality (p<.001) and social functioning (p<.05). In conclusion, dance does not only contribute in the formation of a cultural identity and the perpetual manifestation of customs but also comprises a pleasant kind of exercise, which significantly contributes in emotion management, in social relationships development and in a better quality of life.